Determinasi Profitabilitas Perbankan Swasta di Indonesia: Peran CAR, NPL, Inflasi, dan BI Rate - Putri Marsella Zalianti; Lailatus Sa'adah (Yayasan Literasi Sains Indonesia, 2026)
This study examines the influence of internal and external factors on the profitability of private commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Internal factors include the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL), while external factors consist of inflation and the benchmark interest rate (BI Rate). Profitability is measured using Return on Assets (ROA) to reflect asset management efficiency. Using a purposive sampling method, a sample of 7 banks under the KBMI 3 category was selected. Data were analyzed using panel data regression via the Panel Least Squares (PLS) approach. The findings reveal that CAR has a significant positive effect on ROA, whereas NPL exhibits a significant negative impact. Conversely, inflation and BI Rate show no significant partial effect on ROA. Simultaneously, all four independent variables significantly affect ROA, accounting for 85.67% of the variance. The study's novelty lies in evaluating these combined determinants within private banking post-pandemic. Strategically, banks must optimize capital structure and manage credit risk to sustain long-term profitability.